Anatomical and congenital variations of human dry sternum bone: its embryogenesis and clinical implications - Chakravarthi, Kosuri Kalyan; S., Siddaraju K.; Venumadhav, Nelluri; Bali, Sangeeta Atamaram (International Journal of Research in Medical Sciences, 2017)
Background: The sternum is one of the skeleton parts with frequently detected variation in cross-sectional images or autopsy series. The anatomical or congenital variations of the sternum in the anterior chest wall may involve malignancies, injuries or severe traumas. The aim of the study was undertaken to evaluate the incidence of anatomical and congenital variations of human dry sternum bones. Methods: This study was carried out on 120 dry human sternum bones irrespective of age and sex at Varun Arjun medical college- Banthra, UP, KMCT Medical College, Manassery-Calicut and Melaka Manipal Medical College-Manipal. All the sternum bones were macroscopically inspected for the anatomical and congenital variations of human dry sternum bones. Photographs of the anatomical and congenital variations were taken for proper documentation. Results: Complete sternal foramina in the body of the sternum were noted in 9 bones (7.5%), with an average vertical diameter of 17mm and transverse diameter of 16mm (The highest vertical diameter of 19mm and transverse diameter of 17mm was noted); Incomplete sternal foramina in the body of the sternum were noted in 4 bones (3.3%);Complete sternal foramina in the xiphoid process of the sternum were noted in 7 bones (5.8%) with an average vertical diameter of 6mm and transverse diameter of 8mm; Unusual complete sternal foramina in the body and incomplete sternal foramina in the xiphoid process of the sternum were noted in 8 bones (6.6%); Very rare longer xiphoid process (7.3 cm) with complete sternal foramina was noted in 7 bone (5.8%); Unusual Longer xiphoid process with an average length of 6.7cm with sharp bifid ends was noted in 8 bones (6.6%). Conclusions: The knowledge of existence of anatomical variants and congenital foramina of sternum and xiphoid process found in our study is essential, especially for bone marrow sampling, radiology (X - ray, CT, MRI, and USG) reporting, pathology autopsy and forensic medicine post-mortem reporting and patoacupuncture practice to avoid complications during various surgical procedures.